2022
DOI: 10.3389/fonc.2022.795129
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Immunotherapy for Ovarian Cancer from a Bird’s-Eye Perspective: A Text-Mining Analysis of Publication Trends and Topics

Abstract: ObjectivesOvarian tumors are among the most prominent gynecological malignancies and have a poor prognosis. Immunotherapy has undergone incredible progress in the past two decades. Our study aimed to use a bibliometric approach to identify research trends in ovarian cancer immunotherapy.MethodsLiterature on this topic published from 2000–2020 was retrieved from the Web of Science Core Citation database and analyzed using the bibliometric analysis software VOSviewer and CiteSpace.ResultsA total of 1729 articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Intellectual base and research fronts are two typical indicators of a research program in a research field. 19 The intellectual base refers to all documents that have been cited by corresponding research fields, while the research frontier arises from the intellectual base of this field. Reference of all the academic works in a research field constitutes the foundation of that field.…”
Section: Resultsmentioning
confidence: 99%
“…Intellectual base and research fronts are two typical indicators of a research program in a research field. 19 The intellectual base refers to all documents that have been cited by corresponding research fields, while the research frontier arises from the intellectual base of this field. Reference of all the academic works in a research field constitutes the foundation of that field.…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors do not describe representative articles or clinical trials, which is a slight drawback. Guangyi Jiang and his colleagues depicted geographic trends, subtopic trends, and cluster analysis of immunotherapy in ovarian cancer ( 73 ). They concluded that the PD-1/PD-L1 axis, Tumor Active Tumor-Infiltrating Lymphocytes, and PARP Inhibitor are current hotspots.…”
Section: Discussionmentioning
confidence: 99%
“…The literature included in this study was sourced from the Web of Science Core Collection (WoSCC) database, as it is one of the most systematic and authoritative databases, which is widely recognized for its effectiveness in bibliometric research ( 25 , 26 ). The search was conducted on June 22, 2023, using the following search query: (TS= “Spermatozoa” OR “Sperm” OR “male fertility” OR “male sterility” OR “male reproduction”) AND (TS= “Reactive Oxygen Species” OR “Oxidative stress”).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis aims to help researchers better grasp the research status in this field and overall trends, and provide a reference for future research. most systematic and authoritative databases, which is widely recognized for its effectiveness in bibliometric research (25,26). The search was conducted on June 22, 2023, using the following search query: (TS= "Spermatozoa" OR "Sperm" OR "male fertility" OR "male sterility" OR "male reproduction") AND (TS= "Reactive Oxygen Species" OR "Oxidative stress").…”
Section: Introductionmentioning
confidence: 99%